Carbon-Energy Taxation 2009
DOI: 10.1093/acprof:oso/9780199570683.003.0004
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Competitiveness of Selected Industrial Sectors in ETR Countries

Abstract: The objective of this chapter is to assess whether the carbon‐energy taxes introduced under the environmental tax reforms (ETRs) that were implemented in seven European Union countries between 1990 and 2001 have had any impact on the competitiveness of selected industrial sectors in those countries. Underlying the analyses is a series of country datasets with each dataset containing generic data such as exchange rates and emission factors, and sector‐specific data on energy use, energy prices and taxes, econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Some studies evaluate policies which are closer to the EU ETS such as environmental taxation in some European countries. Miltner and Salmons (2009) studied the impact of environmental tax reforms (ETR) on competitiveness indicators for seven European countries and eight sectors and found that, out of 56 cases, the impact of ETR on competitiveness was insignificant in 80% of cases, positive in 4% and negative for only 16% of the cases (Miltner and Salmons 2009). However, energy-intensive sectors benefited from exemptions and lower rates of taxation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies evaluate policies which are closer to the EU ETS such as environmental taxation in some European countries. Miltner and Salmons (2009) studied the impact of environmental tax reforms (ETR) on competitiveness indicators for seven European countries and eight sectors and found that, out of 56 cases, the impact of ETR on competitiveness was insignificant in 80% of cases, positive in 4% and negative for only 16% of the cases (Miltner and Salmons 2009). However, energy-intensive sectors benefited from exemptions and lower rates of taxation.…”
Section: Literature Reviewmentioning
confidence: 99%